2020
DOI: 10.3390/plants9101297
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation in Nectar Chemistry and Its Implications for Insect Visitors: The Case of the Medicinal Plant, Polemonium Caeruleum L.

Abstract: Floral nectar, being a primary reward for insect visitors, is a key factor in shaping plant–pollinator interactions. However, little is known about the variability in nectar traits, which could potentially affect pollinators and the reproduction of the species. We investigated intraspecific variation in nectar traits in 14 populations of a Red-listed plant, Polemonium caeruleum. Populations varied in terms of the proportion of self-compatible and self-incompatible individuals, and insect communities visiting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 78 publications
(148 reference statements)
0
17
0
Order By: Relevance
“…For example, sucrose-rich nectar has often been recorded in flowers pollinated by hummingbirds and insects with long mouthparts (e.g. long-tongued bees and butterflies), whereas hexose-rich nectars commonly occur in flowers pollinated by shorttongued bees, flies and bats [10][11][12]. In addition to sugars, floral nectar contains small amounts of amino acids, lipids, secondary metabolites and volatile organic compounds, which may influence nectar attractiveness [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, sucrose-rich nectar has often been recorded in flowers pollinated by hummingbirds and insects with long mouthparts (e.g. long-tongued bees and butterflies), whereas hexose-rich nectars commonly occur in flowers pollinated by shorttongued bees, flies and bats [10][11][12]. In addition to sugars, floral nectar contains small amounts of amino acids, lipids, secondary metabolites and volatile organic compounds, which may influence nectar attractiveness [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Nectar is one of the most important food rewards that contain sugar and other constituents such as amino acids, phenolic compounds or alkaloids that are important for pollinators and serve to influence their preferences and behavior (Parachnowitsch et al 2019;Ryniewicz et al 2020). It is, however, a variable trait: in this study, differences in volume and sugar content were found in nectar traits measured between the two populations of P. viridiflora studied, with the highest nectar volume recorded in the Rancho Viejo population.…”
Section: Discussionmentioning
confidence: 59%
“…In P. caeruleum , the lack of specialisation in terms of pollination biology and the spatiotemporal variations in the composition of pollinator assemblages may result in high divergence in flower traits related to pollination. Our previous study on the chemistry of P. caeruleum nectar showed high variability in these traits among populations ( Ryniewicz et al, 2020 ). We also observed some divergence in terms of the anatomy of P. caeruleum flowers, such as differences in flower size or the arrangement of reproductive parts.…”
Section: Discussionmentioning
confidence: 96%
“…According to a previous study on a single population of P. caeruleum , pollen limitation may affect even larger populations of this species ( Zych et al, 2013 ); however, studies involving other populations did not confirm this phenomenon ( Ostrowiecka et al, 2017 ). In addition, these populations differ in terms of insect assemblages visiting flowers ( Zych et al, 2013 ; Ostrowiecka et al, 2017 ) and chemical composition of nectar ( Ryniewicz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%